The Effect of Storage Temperature on the Quality of Pondoh Salak Fruit (Salacca edulis Reinw) - Setya Nugraha, Dwira; Muhammad Abdillah Muyassarun; Naufal Honasan; Dodi Budirokhman (Ann Publisher, 2025)
Salak fruit is known to have many health benefits and is in great demand by the public. Fruits in Indonesia have a low shelf life, such as pondoh snake fruit. So, the temperature during the storage period of salak fruit needs to be considered. This research aims to determine the quality of pondoh salak fruit at different storage temperatures. This research was carried out at the Laboratory of the Faculty of Agriculture, Gunung Jati Swadaya University, Cirebon, West Java. The research was carried out in May – July 2024. The experimental design used was a Completely Randomized Design (CRD). This research consisted of 3 treatments and was repeated 9 times. The observation variables observed were weight loss, fruit hardness, sweetness, and vitamin C. The results showed that storage temperature significantly affected the weight loss and fruit hardness variables.